Inverse relationship between vitamin D levels and platelet indices in Korean adults. Issue 10 (26th November 2017) - Park, Yon Chul; Kim, Jin; Seo, Min Seok; Hong, Sung Won; Cho, Eun Seok; Kim, Jong-Koo
ABSTRACT: Background and aims: Vitamin D deficiency and increased platelet indices are associated with increased rate or risk of several diseases such as cardiovascular disease and metabolic syndrome, respectively. We investigated whether vitamin D deficiency is associated with increased platelet count (PC) and mean platelet volume (MPV). Methods and results: The study included 3190 subjects older than 20 years. Subjects were divided into three groups based on their vitamin D levels: vitamin D deficiency (<10.0 ng/ml); insufficiency (10–20 ng/ml); and sufficiency (>20.0 ng/ml). The associations between platelet indices and various parameters were analyzed by Pearson's correlation analysis and t-tests. Then, multivariate linear regression analyses were done correcting for associated parameters. PC and MPV showed a negative correlation with vitamin D groups by ANOVA and multiple linear regression. PC was inversely related with vitamin D group after adjusting for sex, age, regular exercise, white blood cell count, total cholesterol, hemoglobin, and creatinine levels (β ± SE = −3.461 ± 1.512, P  = 0.022). MPV was also inversely related with vitamin D group after adjusting for regular exercise, hemoglobin level, and total cholesterol level (β ± SE = −0.080 ± 0.026, P  = 0.002), and this relationship remained statistically significant after adjusting for regular exercise, hemoglobin level, total cholesterol level, diabetes, hypertension, and body mass index (β ± SE=−0.082 ± 0.026, P  = 0.002). Conclusion: PC and MPV are inversely associated with vitamin D levels in adults.